Konflik Sosial Masayarakat dalam Perspektif Sosiologi Hukum Islam - Dedi Sumanto (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
Conflicts can be dangerous or may even benefit a relationship, depending on how they are resolved. Because conflict creates strong emotions, emotions are not suitable as a basis for constructive problem solving. Conflict escalation rarely benefits a relationship, especially if it creates selfishness, stubbornness, and withdrawal from relationships. What's worse, conflicts can lead to physical disputes and actual violence, a community can work together, but it can be that at other times the community that has worked together can turn into social conflict. Conversely, people who initially conflict can change to work together for a certain time. For that social processes that occur are very dynamic, these conditions are very dependent on the power management model that runs in the community concerned thus interpreting the conflict based on the causes of conflict are: specific behaviors, norms and personal roles and dispositions. Conflict can also occur in the name of religion, caused by several factors including: superficial religious knowledge, fanaticism, religion as a doctrine, symbols, religious figures, history, fighting for surge.